High content genome-wide siRNA screen to investigate the coordination of cell size and RNA production - Müller, Micha (University of Dundee, 2021)
Coordination of RNA abundance and transcription rates with cell size has been observed in diverse organisms and isogenic cell populations. However, how cells achieve such ‘size-scaling’ of transcription is unknown. Here we describe a genome-wide siRNA screen to find novel regulators of global RNA production in human cells. We quantify single-cell RNA production rates using metabolic pulse-labelling of RNA and subsequent high-content imaging. Our quantitative, single-cell measurements of DNA, nascent RNA, proliferating cell nuclear antigen (PCNA), and total protein, as well as cell morphology and population-context, capture a detailed phenotype of each cell. This allows us to account for changes in cell size and cell-cycle distribution (G1/S/G2) in perturbation conditions, which indirectly affect global RNA production. We also take advantage of the subcellular information to distinguish between nascent RNA localised in the nucleolus and nucleoplasm, to approximate ribosomal and non-ribosomal RNA contributions to the phenotype. The perturbations uncovered through the screen provide a resource for exploring the mechanisms of regulation of global RNA metabolism.
Keywords: FOS: Biological sciences